Impact of COVID-19 on DCMS sectors: First Report. Third Report of Session 2019-21. Report, together with formal minutes relating to the report - Digital, Culture, Media and Sport Committee (2020)
Sport, culture and tourism all operate to some extent by bringing people together for shared experiences. All have been hit hard by the Covid-19 crisis. While this report focuses on sectors within the Department for Digital, Culture, Media and Sport's remit, it is important to remember that their difficulties will spill into the wider economy, and the health and wellbeing of the population as a whole.Recreational and elite sport have been interrupted during the Covid-19 outbreak, with serious financial implications across both sectors. Physical activity is a vital part of the UK's fight against the virus, and we call on Government to ensure that marginalised groups including BAME communities and women are not left behind in efforts to get the UK back to sport and fitness. We also argue that the Covid-19 crisis presents an opportunity for football, in particular, to 'reset' and to introduce essential reforms to financial models, management structures and diversity and inclusion that will benefit the game in the long term.Each year, more people attend the theatre than go to a league football match, yet while considerable effort has been made to resume professional football, the Government's roadmap for when theatres will reopen has been vague and slow-coming. We welcome the Government's announcement of a £1.57 billion support package for the arts, but it was too late for many in the sector and on its own will not be enough to stop mass redundancies and the permanent closure of our cultural infrastructure. We therefore argue that the performing arts need a sector-specific deal that includes:o An extension to the furlough scheme for affected businesses until mass gatherings are permitted under the Government's and Devolved Administrations' Covid-19 guidelines;o Continued workforce support measures, including enhanced measures for freelancers and small companies;o Clear, if conditional, timelines for when they will be able to reopen, and technological solutions to enable audiences to return without social distancing;o Long-term structural support to rebuild audience figures and investment in an uncertain economic climate. This should involve new, sector-specific tax reliefs as well as an extended VAT cut for the sector.Since the start of the outbreak, the tourism sector has been at the mercy of other Departments' announcements on border closures, quarantine periods and 'air bridges'. We call on DCMS to utilise advertising and enhanced data tools to promote 'staycations' and stimulate the return of domestic tourists to our coastal towns and visitor attractions.Finally, we examine how effectively DCMS has advocated for the sectors under its remit during this crisis. With many vital Government support schemes due to end, or not sufficiently covering those working in these sectors in the first place, we argue that DCMS's position within Government, and a fundamental lack of understanding about how DCMS sectors and their workforces are structured, has hampered the support provided by Government during the outbreak. Digital exclusion has left individuals and communities isolated during this crisis, and Ministers told us that although they wanted to do more to help, they have been limited by resources. We therefore call on HM Treasury to ensure DCMS is sufficiently resourced to take the lead on tackling digital exclusion across Government.